Constitutional Values, Legal Politics, and Political Stability: A Comparative Analysis in the Post-Authoritarian Context of Indonesia - Pirdaus, Dede Irman; Chayandari, Rini; Salih, Yasir (International Journal of Humanities, Law, and Politics, 2023)
This paper explores the intricate relationship between constitutional values of equality and justice and their impact on political stability, with a specific focus on Indonesia's post-authoritarian context. Constitutional ideals, while crucial, face challenges in translating into tangible outcomes due to implementation gaps and entrenchment of inequalities. The study employs a comparative analysis of national constitutions, examining cases where provisions of justice and equality either succeeded or failed to foster stable political environments. Pathways linking constitutional equality to political stability are scrutinized, emphasizing both procedural and substantive dimensions. The research employs political stability indicators to unravel the nuanced relationship between constitutional principles and governance outcomes. In the context of Indonesia, the paper delves into the complexities of legal politics during the transition from the New Order to reformasi democracy. The post-authoritarian landscape witnessed struggles for freedom of expression and human rights enforcement, reflecting the challenges of aligning legal frameworks with democratic principles. The analysis considers the uneven progress in rule of law reforms, navigating the legacies of patrimonialism and oligarchic influence